Prayer Warriors: The Story Of The Mamaratbat (Journal of Namibian Studies : History Politics Culture, 2023)
The qualitative study was conducted to determine the practices and beliefs of the mamaratbat and the ways to preserve their culture. Six participants served as key informants on the study, which utilized the multiple case study method. The theories on Functionalism, Habitus and Social Identity were used as frameworks. After a thorough thematic analysis of the data, the following themes emerged: the practice of the mamaratbat is according to catholic rites and is passed down from mother to daughter, they believe in the power of prayers and are written on notebooks handed down from their grandmothers, and lastly, men do not pray for the dead. The study concluded that the practice of the mamaratbat is religious, functional and feminine in nature. And the key to preserving their culture is to preserve the notebooks where the prayers are written.